Clinical prognostic variables in young patients (under 40 years) with hepatitis B virus-associated hepatocellular carcinoma - Wang, Qin; Rahbari, Nuh Nabi (Journal of digestive diseases, 2012)
OBJECTIVE: The aim of this study was to determine the impact of hepatocelluar carcinoma (HCC) screening in chronic hepatitis B patients who did not meet the current screening recommendations. METHODS: Patients who were admitted to Bellevue Hospital Center with HCC were assessed for risk factors, cirrhosis and tumor-specific factors. Eligibility for liver transplantation or resection with favorable outcome was determined by applying Milan criteria. RESULTS: In all 93 patients were diagnosed with hepatitis B virus (HBV)-associated HCC, 18 of whom were under 40 years. Cirrhosis was infrequently associated with HCC in this group, with most cancers occurring in non-cirrhotic patients (12/18, 66.7%). No patient developed HCC outside the American Association for the Study of Liver Diseases (AASLD) cancer screening recommendations (young age, non-cirrhotic) were eligible for liver transplantation or resection with favorable outcomes (within Milan criteria). However, HCC patients who were diagnosed within AASLD screening recommendations did meet Milan criteria in 17.3% (14/81) patients. CONCLUSIONS: Current guidelines for HCC screening in patients with HBV may lead to a delay in diagnosis in non-cirrhotic patients under 40 years. Consideration should be given to modifying current recommendations to advocate entering HBV patients into a cancer-screening program at young age.